PERBANDINGAN OVERRUN, DAYA LELEH, DAN PROTEIN BERBAGAI ES KRIM - Wilna Iznilillah, (Jurnal Ilmiah Pangan Halal, 2021)
Milk is a food product that has good nutritional content for making ice cream. Ice cream is a semi-solid food preparation whose processing is by freezing ice cream flour from a mixture of milk, animal or vegetable fat. The general process of making ice cream is pasteurization, homogenization, cooling, stirring, and the addition of other ingredients. These affect the overrun value, melting power and protein of the resulting. Overrun or degree of development is the percentage of volume expansion, namely the increase in the volume of ice cream between before and after freezing. Melting power is the time it takes for ice cream to melt completely. Protein is a nutrient or macro component needed by all ages. The ingredients used as ice cream products include bananas, stone banana flour, plantain skin, durian seeds, green beans, campedak, purple sweet potato, tempeh and ginger, mangosteen peel, edamame, vanilla and coconut milk, dragon fruit and mustard greens, Soursop puree and soursop leaf extract, papaya, cowpea, corn porang flour, green beans, honey, suji gumbili leaf, mangrove fruit puree, winged bean, and sweet potato have different overrun values, melting power, and protein. These differences can be influenced by different types of milk, and methods used in the process of making ice cream.